Patient participation in postoperative care activities in patients undergoing total knee replacement surgery: Multimedia Intervention for Managing patient Experience (MIME). Study protocol for a cluster randomised crossover trial - McDonall, Jo (BMC Musculoskelet Disord, 2016)
BACKGROUND: Patient participation is an important indicator of quality care. Currently, there is little evidence to support the belief that participation in care is possible for patients during the acute postoperative period. Previous work indicates that there is very little opportunity for patients to participate in care in the acute context. Patients require both capability, in terms of having the required knowledge and understanding of how they can be involved in their care, and the opportunity, facilitated by clinicians, to engage in their acute postoperative care. This cluster randomised crossover trial aims to test whether a multimedia intervention improves patient participation in the acute postoperative context, as determined by pain intensity and recovery outcomes. METHODS/DESIGN: A total of 240 patients admitted for primary total knee replacement surgery will be invited to participate in a cluster randomised, crossover trial and concurrent process evaluation in at least two wards at a major non-profit private hospital in Melbourne, Australia. Patients admitted to the intervention ward will receive the multimedia intervention daily from Day 1 to Day 5 (or day of discharge, if prior). The intervention will be delivered by nurses via an iPad™, comprising information on the goals of care for each day following surgery. Patients admitted to the control ward will receive usual care as determined by care pathways currently in use across the organization. The primary endpoint is the “worst pain experienced in the past 24 h” on Day 3 following TKR surgery. Pain intensity will be measured using the numerical rating scale. Secondary outcomes are interference of pain on activities of daily living, length of stay in hospital, function and pain following TKR surgery, overall satisfaction with hospitalisation, postoperative complications and hospital readmission. DISCUSSION: The results of this study will contribute to our understanding of the effectiveness of interventions that provide knowledge and opportunity for patient participation during postoperative in-hospital care in actually increasing participation, and the impact of participation on patient outcomes. The results of this study will also provide data about the barriers and enablers to participation in the acute care context. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12614000340639 Trial Registration date 31/03/2014.